PENGARUH PRAKTIK KERJA INDUSTRI, PRESTASI BELAJAR MATA PELAJARAN PRODUKTIF DAN MINAT BERWIRAUSAHA TERHADAP KESIAPAN KERJA SISWA SMK NEGERI KOMPETENSI KEAHLIAN TEKNIK KENDARAAN RINGAN DI KOTA MAKASSAR - Yermia Yunus; Abdul Muis Mappalotteng; Syafiuddin Parenrengi (UNM Journal of Technology and Vocational, 2023)
SMK is a vocational secondary education, which aims to prepare students to become professional workers to work in certain fields. The results of preliminary observations indicate that the students’ work readiness at SMKN in Light Vehicle Engineering Competency in Makassar City is still not optimal. The purpose of this study is to discover the description of industrial apprentice, learning achievement in productive subjects, entrepreneurship interest, and work readiness as well as to analyze the influence of industrial apprentice, learning achievement in productive subjects, and entrepreneurship interest on students’ work readiness at SMKN in Light Vehicle Engineering Skills Competency in Makassar City partially and simultaneously. This study is a type of ex post facto research with a quantitative approach. The research population were students of SMKN in Light Vehicle Engineering Competency in Makassar City. The sampling technique employed proportional random sampling technique with 122 students. Data collection techniques were conducted by employing questionnaires and documentation, while data analysis were conducted by employing descriptive statistical analysis and inferential statistical analysis. The results of the study reveal that the level of industrial apprentice is categorized in good category by 91%, learning achievement in productive subjects is categorized in good category by 89%, entrepreneurship interest is categorized in high category by 86%, and work readiness is categorized in high category by 84%. There is a positive and significant influence of industrial apprentice, learning achievement of productive subjects, and entrepreneurship interest on students’ work readiness partially 61%, 77.5%, 29% respectively, and 85.3% simultaneously.